Follow your heart: Survival chances and costs after heart attacks - An instrumental variable approach - Alice Sanwald; Thomas Schober (Johannes Kepler Universität Linz, Christian Doppler Laboratory Aging, Health and the Labor Market, 2014)
We analyze mortality and follow-up costs of heart attack patients using administrative data from Austria from 2002-2011. As treatment intensity in a hospital largely depends on whether it has a catheterization laboratory, we focus on the effects of patients' initial admission to these specialized hospitals. To account for the nonrandom selection of patients into hospitals, we exploit individuals' place of residence as a source of exogenous variation in an instrumental variable framework. We find that the initial admission to specialized hospitals increases patients' survival chances substantially. The effect on 3-year mortality is -9.5 percentage points. A separation of the sample into subgroups shows the strongest effects in relative terms for patients below the age of 65. We do not find significant effects on longterm inpatient costs and find only marginal increases in outpatient costs.
Keywords: I11; I12; 330; Acute myocardial infarction; mortality; costs; instrumental variables